Groundwater pumping by heterogeneous users - Saak, Alexander E.; Peterson, Jeffrey M. (My University, 2012)
Farm size is a significant determinant of both groundwater irrigated farm acreage and groundwater irrigation application rates per unit land area. This paper analyzes the patterns of groundwater exploitation when resource users in the area overlying a common aquifer are heterogeneous. In the presence of user heterogeneity, the common resource problem consists of inefficient dynamic and spatial allocation of groundwater because it impacts income distribution not only across periods but also across farmers. Under competitive allocation, smaller farmers pump groundwater faster if farmers have a constant marginal periodic utility of income. However, it is possible that larger farmers pump faster if the Arrow-Pratt coefficient of relative risk-aversion is sufficiently decreasing in income. A greater farm-size inequality may either moderate or amplify income inequality among farmers. Its effect on welfare depends on the curvature properties of the agricultural output function and the farmer utility of income. Also, it is shown that a flat-rate quota policy that limits the quantity of groundwater extraction per unit land area may have unintended consequences for the income distribution among farmers.
Keywords: Agriculture; Conceptual models; Groundwater management